Global Spinal Alignment in Patients With Cervical Spondylotic Myelopathy. Issue 3 (1st February 2018) - Yoshida, Go; Alzakri, Abdulmajeed; Pointillart, Vincent; Boissiere, Louis; Obeid, Ibrahim; Matsuyama, Yukihiro; Vital, Jean Marc; Gille, Olivier
Abstract : Study Design: A prospective radiographic analysis of cervical spondylotic myelopathy (CSM). Objective: The aim of this study was to clarify the pathophysiology of CSM, and use the characteristic of global spinal alignment for determining the surgical strategy. Summary of Background Data: Radiographic evaluation of CSM, in general, comprises cervical magnetic resonance imaging (MRI) and regional cervical radiography, which cannot distinguish between cervical hyperlodorsis with spinopelvic compensation and cervical lordorsis with normal global alignment. Methods: Our inclusion criteria were preoperative whole spine radiography and cervical MRI and health-related quality of life scores. Global spinal alignment was characterized by cervical lordosis (CL), C7 sagittal vertical axis (SVA), T1 slope (T1S), thoracic kyphosis (TK), lumbar lordosis (LL), pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS), and knee flexion angle (KFA). Cervical alignment was characterized by O-C2, C2–4, C5–7, and C2–7 angles; cranial center of gravity (CCG) C7SVA; and C2–7 SVA. Responsible lesion determined using MRI was divided from C2/3 to C7/T1. Results: Eighty-eight surgically treated CSM patients with EOS full spine imaging were prospectively analyzed. There were 72 normal (Type 1; SVA <50 mm) and 16 positive (Type 2; SVA ≥50 mm) global balance patients. There were significant differences in age, T1S, KFA, T1S-CL, SVA, CCG-SVA, and C2–7 SVA between Type 1 and Type 2. C3/4 lesion was more common in Type 2 than in Type 1. There was a positive correlation between global sagittal, but not regional, balance, and responsible lesion. C3/4 lesion was more frequent in older, male, high SVA, large T1S-CL, large KFA, and large cranial lordosis (C2–4/C5–7 angle) patients. Conclusion: This study indicates the necessity for global alignment evaluation, particularly in older CSM patients because of their compensation mechanism for global malalignment. Surgical strategy for cranial type CSM should be carefully selected considering global balance. Level of Evidence: 4